Variability of airborne microbiome at different urban sites across seasons: a case study in Rome - Pollegioni, Paola; Cardoni, Simone; Mattioni, Claudia; Piredda, Roberta; Ristorini, Martina; Occhiuto, Donatella; Canepari, Silvia; Korneykova, Maria V.; Soshina, Anastasia S.; Calfapietra, Carlo; Gavrichkova, Olga (Frontiers in Environmental Science, 2023)
Biogenic fraction of airborne PM10 dominated by bacteria and fungi, has been recognized as serious environmental and human health issues in cities. In the present study, we combined a high-throughput amplicon sequencing of the bacterial 16S rRNA gene and the fungal internal transcribed spacer (ITS) region, with elemental analysis of airborne particulate matter (PM10) to investigate the community compositions and structures of PM10-associated bacteria and fungi across four different seasons in three urban sites of Rome with differential pollution rate. In this study, а clear seasonal shift of bacterial and fungal community structure driven by PM10 mass concentrations and environmental factors, such as temperature and precipitations, has been identified. In addition, the seasonal impact of local sources and long-range transported air masses on the community structures of the microbes has been also postulated. Our data revealed that the lack of precipitation and the subsequent resuspension of dust produced by vehicular traffic might contribute to the maximum abundance of soil-associated microbes in winter and summer. However, the increase of PM10 concentrations favoured also by climatic conditions, domestic heating and dust advection event from African desert further shaped the community structure of winter. Across three seasons, the pollutant removal-hydrogen oxidation bacteria and the opportunist-human pathogenic fungi progressively increased with pollution levels, in the sequence from green to residential and/or polluted area close to the traffic roads, with highest fraction during winter. Hence, our results highlight a close interrelationship between pollution, climatic factors and abundance of certain bacterial and fungal predicted functional groups also with potential implications for human health.